Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi Menggunakan Electronic Filing - Setiadi, Agnya Salsabila; Sari, Ervina Indri; Adnyana, I Gede Sudi (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Tax Reporting, E-Filing and Personal Taxpayers _______257 Submitted FEBRUARY 2024 Accepted JULY 2024 JABKES Jurnal Aplikasi Bisnis Kesatuan Vol. 4 No. 2, 2024 page. 257-262 IBI Kesatuan ISSN 2807 – 6036 DOI: 10.37641/jabkes.v4i2.2010 KPP Pratama Ciawi is a tax office that operates in general and aims tcollect revenue through tax reporting activities. Annual SPT reporting is an obligation that must be carried out by individual taxpayers. In the digital era, electronic filing, or E-filing, has become an alternative introduced by the Directorate General of Taxes to simplify the online tax reporting process. The purpose of this research is to review the procedure for reporting the annual SPT of individual taxpayers using E-filing. The results of this study indicate that E-filing provides many advantages for individual taxpayers. The reporting process can be carried out flexibly and efficiently without the need to queue at the tax office. In addition, E-filing allows taxpayers to fill out and send annual tax returns in real time via electronic devices such as computers, laptops, or smartphones. Keywords: Tax Reporting, E-filing